Skin cancer – epidemiological, clinical and surgical treatment analysis of 1406 patients - Włodarkiewicz, Adam; Kozicka, Dorota; Michajłowski, Igor; Sobjanek, Michał; Niekra, Marcin; Nałęcz, Dariusz (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Non melanoma skin cancers are the most common malignancies in the Caucasian population. The incidence is increasing rapidly. Surgery is the most effective management. Objective . Epidemiological, clinical and surgical treatment efficacy analysis of cases treated in Gdańsk. Material and methods . 1406 patients with 1849 lesions (691 men and 715 women) were analysed. Patients between 1998 and 2009 underwent surgery. Tumours were excised with a standard margin. The following patient and tumour characteristics were recorded: age, gender, anatomical location, tumour size, excisional margins, type of reconstruction and relapses. Results . The number of patients operated on during 12 years increased. Average age was 66. BCC/SCC ratio was 9:1. The facial area was the most frequent tumour site. High-risk cancers were observed in 1020 patients. Recurrence rate was 3.7% for all tumours and 5.2% for high-risk skin cancers. Conclusions . The incidence of skin cancers in the northern Polish population is increasing. Surgical treatment should be a “gold standard” for high-risk tumours.